PENGARUH KEBIJAKAN TUNJANGAN PERBAIKAN PENGASILAN PEGAWAI (TPP) TERHADAP KINERJA DAN PROFESIONALISME GURU HONORER KABUPATEN KLATEN - Itok Dwi Kurniawan (Universitas Muhammadiyah Mataram, 2022)
This study aims to determine the effect of the salary allowance policy as a form of appreciation for the hard work of the teachers. In this case, honorary employees, who have provided learning and carry out their responsibilities as teachers. The salary contribution will improve the performance and professionalism of honorary teachers in the teaching and learning process in the classroom. Teacher performance and professionalism is very important and needs to be considered in the development of human resources, because the success of an education cannot be separated from quality human resources. The population of this study were honorary teachers in Klaten Regency who were selected as honorary teachers with salaries obtained from committee assistance and school administration. The research method used is survey research. Data collection is done by using a questionnaire that has been tested. The results of the study indicate that there is a positive and significant influence between the policy of improving allowances for improving employee earnings on the performance and professionalism of teachers. For this reason, it is necessary to have a policy to improve teacher performance and professionalism, to increase the policy for improving employee morale allowances (TPP) in Klaten Regency, Central Java.